Effort Management Tourism Objective Through The Existence of Social Groups in The Community - Jumriani; Muhaimin, Muhammad; Abbas, Ersis Warmansyah; Mutiani; Rusmaniah (School of Business, IPB University (SB-IPB), 2022)
The tourist attraction is developed synergistically by developing tourist facilities, public facilities, infrastructure, and community empowerment in a complete and sustainable system. In Banjarmasin City, in Banua Anyar Village, tourism management is carried out with community involvement in synergy with the Government through tourism awareness groups known as Pokdarwis. The purpose of writing this article is to identify the management of tourism objects through the existence of social groups. The approach used in this research is qualitative with a descriptive method. The data collection technique was carried out through observations in the culinary tourism area in the Banua Anyar Culinary Area. The results of the study ensure that the management of tourism objects through Pokdarwis in Banua Anyar Village is carried out in three forms of activity, namely the realization of Sapta Pesona, providing facilities and infrastructure and increasing knowledge of the community around tourism objects. These activities need to be carried out so that the existence of Pokdarwis can determine realistic strategic steps to realize the vision and carry out the mission of the existence of the government and the community in managing tourism objects through the existence of social groups. Therefore, it can be concluded that the existence of Pokdarwis in Banua Anyar Village is a form of real effort from the authority to the region to plan, develop and manage tourism in the region. So that local people get the opportunity to get involved in tourism development. Keywords: management, tourism objects, social groups, pokdarwis, tourism development